2022
DOI: 10.3390/ani12212989
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of miRNA-mRNA in Ovarian Granulosa Cells Treated with Kisspeptin in Tan Sheep

Abstract: Kisspeptin is a peptide hormone encoded by the kiss-1 gene that regulates animal reproduction. Our studies revealed that kisspeptin can regulate steroid hormone production and promote cell proliferation in ovarian granulosa cells of Tan sheep, but the mechanism has not yet been fully understood. We speculated that kisspeptin might promote steroid hormone production and cell proliferation by mediating the expression of specific miRNA and mRNA in granulosa cells. Accordingly, after granulosa cells were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…MiR-let-7c is one of the earliest identified miRNAs [53], and its family members are highly conserved across species and the most abundant miRNAs in the ovary [54,55], suggesting that they have fundamental roles in reproductive physiology. Here, miR-let-7c was observed during all phases of the canine estrous cycle, which agrees with the presence of miR-let-7c in the ovine [56] and caprine [57] granulosa cells. The lowest miR-let-7c expression level was observed in the estrus phase, while the relative gene expression of ESR2, the predicted target of miR-let-7c, was the highest.…”
Section: Discussionsupporting
confidence: 87%
“…MiR-let-7c is one of the earliest identified miRNAs [53], and its family members are highly conserved across species and the most abundant miRNAs in the ovary [54,55], suggesting that they have fundamental roles in reproductive physiology. Here, miR-let-7c was observed during all phases of the canine estrous cycle, which agrees with the presence of miR-let-7c in the ovine [56] and caprine [57] granulosa cells. The lowest miR-let-7c expression level was observed in the estrus phase, while the relative gene expression of ESR2, the predicted target of miR-let-7c, was the highest.…”
Section: Discussionsupporting
confidence: 87%
“…Kp neuropeptide regulates the in vitro production of bovine embryos without the addition of LH and FSH (Soares et al, 2018). Downregulate of miRNA-1246 expression due to Kp, leads to the synthesis of progesterone in cattle (Guo et al, 2022) [52] .…”
Section: Cattlementioning
confidence: 99%
“…The addition of other reproductive hormones (FSH, LH, and E2) in IVM media supplemented with oocytes clearly demonstrated that not only does Kp act on oocyte maturation but also rise the first polar body extrusion and cumulus cell expansion rate (Byri et al, 2017) [50] . The Kp-treated granulosa cell of RNA sequence revealed that expression of the different kinds of miRNA and mRNA is associated with the mechanism of steroid hormone regulation, cell proliferation, and physiological functions of ovarian granulosa cells in Tan sheep (Dai et al, 2022) [52] . The different kinds of doses and modes of Kp injection can change the gonadotropic hormone response and cause ovulation in noncyclical female ewes (Caraty et al, 2007) [51] .…”
Section: Sheepmentioning
confidence: 99%